Short and Medium-Term Evaluation of Patients in Coronary Post-Angioplasty: Préliminary results at the Cardiology Department of the Hospital University Aristide Le Dantec of Dakar (Senegal): Study on 38 Cases - M, Dioum; F, Aw; K, Masmoudi; ND, Gaye; SA, Sarr; SCT, Ndao; J, Mingou; AA, Ngaidé; B, Diack; M, Bodian; MB, Ndiaye; MB, Ndiaye; et al. (Journal of Cardiology and Cardiovascular Medicine, 2017)
Introduction: Coronary angioplasty is a safe therapeutic method for coronary disease. However, its major obstacles remain the occurrence of stent thrombosis (ST) and in-stent restenosis (ISR). The aim of this study was to evaluate the short-term and medium-term results of coronary angioplasty patients in the cardiology department of Aristide Le Dantec hospital in Dakar. Methodology: It was a longitudinal, descriptive and analytical study over a period of 12 months (April 2014 to April 2015) with a follow-up at 6 months. Was included any patient who had a coronary angioplasty with stent placement. Results: Thirty-eight patients had been included with a male predominance and a sex ratio of 5.32. The average age was 57.94 years. Cardiovascular risk factors were mainly smoking (57.9%) and coronary heredity (42.1%), followed by hypertension (39.5%) and diabete (34.2%). The indications for angioplasty were acute coronary syndromes TS(+) and TS(-) respectively (50%) and (23.7%) and stable angina (26.3%). The right femoral approach was almost exclusive (97.4%). Coronary angiography revealed a predominance of anterior interventricular affection (84.2%). Type B lesions were the most frequent (68.4%). The single-truncal valve affection was predominant (76.3%). Direct stenting accounted for 63.2% of procedures. Twenty-one bare stents (55.3%) and 17 active stents (44.7%) were implanted. The results were excellent (94.7%). One case of acute stent thrombosis was noted. Echocardiography of dobutamine stress during follow-up was positive in 04 patients (12.5%). The control coronary angiography performed in two patients revealed an ISR. The predictive factors for restenosis were dominated by a deterioration in the segmental kinetics (p=0.009), in the diastolic function (p=0.002), the systolic function (p=0.003), a high post angioplasty troponin (p=0.004), the presence of calcifications (p=0.004) and a high SYNTAX score (p=0.021). Conclusion: According to these results, Angioplasty is an effective therapy for coronary disease. However, a correct intake of double platelet antiaggregants and clinical and non-invasive screening are required for follow-up to avoid stent thrombosis or restenosis.